Makerspaces in the early years: Enhancing digital literacy and creativity (MakEY) ... - Marsh, Jacqueline; Dr Hans Christian Arnseth; Beech, Annie; Bishop, Julia; Dr Alicia Blum-Ross; Chesworth, Elizabeth; Dýrfjörð, Kristín; Ellis, Heather; Professor Ole Erstad; Fashanu, Christina; Dr Torfi Hjartarson; Hreiðarsdóttir, Anna Elisa; et al. (Figshare, 2019)
This collection of data is related to the EU-funded project ‘Makerspaces in the early years: Enhancing digital literacy and creativity’ (Grant number 734720). The website for the project is: https://makeyproject.eu The project involved seven European countries (Denmark, Finland, Germany, Iceland, Norway, Romania, UK) and the USA. The research questions were as follows: Personal level What are the beliefs and practices of makerspace employees and volunteers, and early years practitioners, across Europe with regard to the value and development of makerspaces for the 3-8 age group? What are the meanings and motivations children attach to their engagement in making activities in each of the case study settings, and how do these motivations interact with the demands of the makerspace? How are children’s experiences in the makerspace reshaping their interests in and identifications with digital literacy learning and creativity? What kinds of digital literacy skills and creative competences do children develop ...